Hemodynamic impact of molecular adsorbent recirculating system in refractory vasoplegic shock due to calcium channel blocker poisoning. Issue 12 (December 2021) - Beyls, Christophe; Malaquin, Stéphanie; Huette, Pierre; Mary, Aurélien; Besserve, Patricia; Roger, Pierre-Alexandre; Bernasinski, Michaël; Guilbart, Mathieu; Abou-Arab, Osama; Dupont, Hervé; Mahjoub, Yazine
Objective: To report the hemodynamic effect of to the molecular adsorbent recirculating system (MARS™) therapy for patients in refractory vasoplegic shock due to calcium channel blocker (CCB) poisoning Methods: We report a retrospective cohort of patients who were hospitalized for CCB poisoning with refractory vasoplegic shock and treated by MARS therapy, at Amiens Hospital University, from January 2010 to December 2019. Improvement in hemodynamic was assessed by dynamic changes in mean arterial pressure (MAP) and norepinephrine levels over a 24-h period after MARS therapy. Cardiac function was assessed by transthoracic echocardiography. Results: MARS therapy was performed on seven patients for CCB poisoning. CCB poisoning included nicardipine ( n  = 3, 43%) amlodipine ( n  = 3, 43%), and verapamil ( n  = 1, 14%). The median time to start MARS therapy was 24 [14–27] h after drug ingestion and 6 [2–9] h after ICU admission. Cardiac output was preserved for all patients. MAP values improved from 56 [43–58] to 65 [61–78] 16 mmHg ( p  = 0.005). Norepinephrine dose significantly decreased from 3.2 [0.8–10] µg/kg/min to 1.2 [0.1–1.9] µg/kg/min ( p  = 0.008) and lactate level decreased from 3.2 [2.4–3.4] mmol/l −1 to 1.6 [0.9–2.2] mmol/l −1 ( p  = 0.008). The median length of ICU stay was 4 (2–7) days and hospital stay was 4 (4–16) days. No complication related to the MARS therapy were reported. No patient died and all were discharged from the hospital. Conclusion: We reported the largest case-series of MARS therapy for refractory vasoplegic shock due to CCB poisoning. We observed that MARS therapy was associated with an improvement of hemodynamic parameters.